2014
DOI: 10.1002/2014jc009810
|View full text |Cite
|
Sign up to set email alerts
|

Southern Ocean jets and how to find them: Improving and comparing common jet detection methods

Abstract: This study undertakes a detailed comparison of different methods used for detecting and tracking oceanic jets in the Southern Ocean. The methods under consideration are the gradient thresholding method, the probability density function (PDF) method, and the contour method. Some weaknesses of the gradient thresholding method are discussed and an enhancement (the WHOSE method), based on techniques from signal processing, is proposed. The WHOSE method is then compared to the other three methods. Quantitative comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(80 citation statements)
references
References 66 publications
(147 reference statements)
2
77
1
Order By: Relevance
“…These include changes in the ocean heat content in the upper ocean between the 1930s-1950s and the 1990s (e.g., Böning et al, 2008;Gille, 2008), increases in the heat content of deep water between the 1990s and 2005 (e.g., Purkey and Johnson, 2010), and increases in eddy kinetic energy in the Indian and Pacific oceans since 1993 (Hogg et al, 2015). Observational evidence of shifts in the winds, however, indicates that while there may be a slight southward shift in winds during the Southern Hemisphere summer, the overall yearly average shift is not significant (Swart and Fyfe, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These include changes in the ocean heat content in the upper ocean between the 1930s-1950s and the 1990s (e.g., Böning et al, 2008;Gille, 2008), increases in the heat content of deep water between the 1990s and 2005 (e.g., Purkey and Johnson, 2010), and increases in eddy kinetic energy in the Indian and Pacific oceans since 1993 (Hogg et al, 2015). Observational evidence of shifts in the winds, however, indicates that while there may be a slight southward shift in winds during the Southern Hemisphere summer, the overall yearly average shift is not significant (Swart and Fyfe, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…procedure (e.g., Sallée et al 2008a;Dufour et al 2011;Langlais et al 2011;Dufour et al 2013) that reconciles the hydrographic and dynamical views of the fronts (Langlais et al 2011;Chapman 2014). More precisely, for each front the method identifies a single SSH contour based on hydrographic criteria (e.g., temperature and salinity) and dynamic criteria (e.g., transport and SSH gradients).…”
Section: B Definition Of Acc Front Pathsmentioning
confidence: 99%
“…More precisely, for each front the method identifies a single SSH contour based on hydrographic criteria (e.g., temperature and salinity) and dynamic criteria (e.g., transport and SSH gradients). For a review and comparison of the strength and weaknesses of the various jet detection methods, the reader is referred to Chapman (2014).…”
Section: B Definition Of Acc Front Pathsmentioning
confidence: 99%
“…These fronts are prone to merging and separations as part of the intense eddy activity observed along the ACC. A number of frontal definitions were later proposed based on this same idea (Boning et al 2008;Sallée et al 2008;Langlais et al 2011;Chapman 2014;Kim and Orsi 2014), and it was found that SSH satellite observations were very useful to track fronts and eddies.…”
Section: Introductionmentioning
confidence: 99%